Comparative study of sewage water and well water irrigation in the peri-urban area of Nag river in Nagpur district - MHASKE, A.R.; PANGUL, C.S.; MHASKE, TUSHAR (Journal of Soil and Water Conservation, 2024)
Long-term irrigation with sewage water adds large amounts of carbon, major and micro- nutrients to the soil. In the present study, effect of sewage water irrigation on soils and crops along with their associated effect on ground (well) water after about three decades of irrigation with domestic sewage effluent as a function of distance from the disposal point was studied. Use of sewage for irrigation improved the organic carbon to 7.27–7.78 g kg-1 and fertility status of soils especially down to a distance of 1 km along the disposal channel. Build-up in available N was up to 261.10 kg ha-1, available P (55.88 kg ha-1) and available K (562.18 kg ha-1) in surface 0.20 m sewage irrigated soils. Traces of Cl- (29.13 mg l-1), SO4 2- (10.78 mg l-1), Mg2+ (10.40 mg l-1), Na+ (18.50 mg l-1) and K+ (3.59 mg l-1) could also be observed in well waters near the disposal point thus indicating initiation of ground water contamination. However, the contents of heavy metals in crops sampled from the area were below the permissible critical levels. Though the study confirms that the domestic sewage can effectively increase water resource for irrigation but there is a need for continuous monitoring of the concentrations of potentially toxic elements in soil, plants and ground water.